2006 International Conference on Information and Communication Technologies and Development 2006
DOI: 10.1109/ictd.2006.301873
|View full text |Cite
|
Sign up to set email alerts
|

A Fragile Link: Disaster Relief, ICTs and Development

Abstract: When disasters strike and aid agencies pour in to help the survivors they are increasingly making use of advanced information and communication technologies (ICTs). For remote areas of developing countries, this use of ICTs may be the community's first exposure to these technologies. And while the role of these ICTs is primarily linked to disaster response and recovery, in certain situations they can be transitioned for use in development programs. This paper discusses the crucial factors in design and deploym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The study showed that insufficient ICT deployment in emergency management was discovered in this study. This agrees with the findings of Maitland, Pogrebnyakov and Van Gorp (2006), who observed that ICT deployments within an organisation are challenging. Also, the study is in line with the results of Bayiah and Kuo (2010), which showed that national actors use the radio and local TV for disaster preparedness and mobile phones for disaster response, while the Internet, fixed phone and fax had a very low usage rate or sometimes not used at all.…”
Section: Research Findings and Discussionsupporting
confidence: 92%
“…The study showed that insufficient ICT deployment in emergency management was discovered in this study. This agrees with the findings of Maitland, Pogrebnyakov and Van Gorp (2006), who observed that ICT deployments within an organisation are challenging. Also, the study is in line with the results of Bayiah and Kuo (2010), which showed that national actors use the radio and local TV for disaster preparedness and mobile phones for disaster response, while the Internet, fixed phone and fax had a very low usage rate or sometimes not used at all.…”
Section: Research Findings and Discussionsupporting
confidence: 92%
“…This could include the adoption of standards and norms from healthcare or emergency management in ways that benefit all stakeholders. While leapfrogging is not as common in disaster response as in other disciplines, there is precedent for technology leapfrogging in disaster data collection and data sharing ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid emergency response adds an additional layer of complexity and difficulty to ICTD projects and research [20]. Ken Banks and the creators of FrontlineSMS first applied an SMS-based reporting system to crowdsource election monitoring in Nigeria in 2007 [1].…”
Section: Relevance To Ictdmentioning
confidence: 99%